Evolution of Increased Volcanic Activity in Arjuno-Welirang Based on LST Analysis of Landsat 8 Satellite Imagery Using GEE Cloud Computing - Suaidi , Daeng Achmad; Maryanto, Sukir; Rahadi Santoso, Didik; Naba, Agus; Hasan, Muhammad Fathur Rouf; Zulaikah, Siti; Ahmad, Mustaffa Anjang; Zainorabidin, Adnan (International Journal of Integrated Engineering, 2023)
Typically, monitoring the volcanic activity of a volcano is carried out using volcanic seismic methods. However, this method is technically less flexible. Volcano seismic data is not freely available. Access to these data centers must be authorized by the data authority. Therefore, it is necessary to use other methods as an alternative. The alternative method used in this study is remote sensing using the Landsat 8 satellite sensors. Landsat 8 satellite imagery data can be freely accessed and easily downloaded. Landsat 8 image analysis is implemented with Google Earth Engine (GEE). GEE is a remote sensing image analysis programming tool with a cloud computing platform. The GEE programming implementation is open source. With GEE, the evolution of Arjuno-Welirang volcanic activity can be monitored accurately. The use of GEE with a cloud computing platform also makes it easier to process large remote sensing data because the downloaded file's size is unlimited. GEE has successfully conducted an LST analysis on Landsat 8 satellite imagery of the Arjuno-Welirang complex area in the 2016-2021 range. The LST calculation is performed by adding the surface emissivity correction obtained based on the NDVI value. According to the results of the LST calculations that have been obtained, the surface temperature in the Arjuna Welirang Crater area experienced the highest increase in 2018, reaching 33.94 oC, with a larger contour size of thermal distribution image than the others. This increase in thermal based volcanic activity is in accordance with the increase in seismic activity monitored by the VSI (Volcanological Survey of Indonesia).